Makna dan Klasifikasi Amanah Qur’ani Serta Relevansinya dengan Pengembangan Budaya Organisasi - Rahmad Hakim; Adib Susilo (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Amanah has a significant role in Islam. In some mandate authority, amanah is one of the conditions that must be fulfilled. This study aims to conduct an in-depth analysis related to the meaning of the mandate and its classification in relation to the development of organizational culture. This research is qualitative with documentation as the technique of collecting data. This technique is carried out by examining documents related to the interpretation of the mandate through several interpretive literatures and also other works. The conclusion of the study states that the meaning of amanah is obedience, security, and keeping promises. Furthermore, the classification of amanah in the context of developing organizational culture is as a criterion for faith, a criterion for choosing colleagues, as an organizational culture, and as one of the criteria for the success of a believer. Thus, the Qur’anic meaning and classification of amanah play a role in enriching the development of organizational culture in thedisruptive era